Kinematic characteristics in patients with subcortical vascular cognitive impairment: a quantitative analysis of digitized spiral drawing metrics - Hyo Jeong Kim; Hyemin Jang; Hee Jin Kim; Duk L. Na; Ji Hye Yoon (Scientific Reports)
Abstract Subcortical vascular cognitive impairment (SVCI) is caused by white matter degeneration. Multiple lacunar infarction due to deep small vascular disease around the subcortical structure and incomplete infarction of white matter owing to decreased perfusion are some of the causes of vascular cognitive impairment. Damage to subcortical structures and prefrontal-cortical circuits can affect motor skills along with cognitive abilities. In this study, we identified the indicators, such as pen pressure, speed, and deviation (degree of deviation from the target line), which can be observed in drawing performance in patients with SVCI. A total of 24 patients with SVCI and 26 healthy adults (HC) were subjected to digitized drawing along straight lines and spiral drawing (drawing along spiral lines, free spiral drawing). In the drawing along straight lines, the SVCI group showed a greater deviation than the HC group. In the drawing along spiral lines, the SVCI group showed greater pen pressure and deviation than the HC group. In the free spiral drawing tasks, the SVCI group showed greater pen pressure and deviation than the HC group. In the free spiral drawing task, the deviation of the SVCI group increased as the wheels of the spiral increased in the clockwise and counterclockwise directions. The SVCI group showed greater pressure to hold and press pencils during drawing compared to HC due to damage to cognitive and motor skills; Further, it deviated from the provided target line. These results may be due to complex cognitive-motor deficits, motor patterns, or impaired motor termination and conversion following damage to the frontal-subcortical circuit. This study provides essential clinical basic data that can be utilized to precisely determine the diminished kinematic behavior within the SVCI group.